The effect of Leucaena leucocephala on beef production and its toxicity in the Chaco Region of Argentina - Radrizzani Bonadeo, Alejandro; Nasca, Jose Andres (CIAT, 2020)
Hedgerows of the fodder tree legume, Leucaena leucocephala ssp. glabrata (leucaena), planted with a companion grass, provide productive, profitable and sustainable tropical pasture (Shelton and Dalzell 2007). Although leucaena can improve beef production, poor grower adoption has limited development of leucaena in the Chaco Region of Argentina. Factors contributing to poor adoption include: (1) unsuccessful establishment; (2) limited understanding of leucaena management as a forage resource; and (3) concerns about mimosine toxici-ty. While these 3 limitations have been overcome in other regions of the world (e.g. northern Australia and the Chaco Region of Paraguay), in Argentina little is known about leucaena management and the protection of ruminants against mimosine toxicosis.